Arquitetura e urbanismo - Maraschin, Dra. Arq. Clarice (Universidad Nacional del Litoral, 2014)
This work, based upon a reflection on teaching practices, debates the conceptual and methodological challenges present nowadays to urban planning teaching in this transition from methods and organizational structures based upon functionalist-comprehensive planning. It is an attempt to debate the link between (i) the recent vision which incorporates the complexity theory to understand and plan the city; (ii) the limitations, and possibilities of thought and intervention using complex systems due to new urban planning interpretation in a defying urban environment, and, (iii) the challenges to urban planning teaching revision in graduate architecture schools and a need for new methodologies and approaches to doing that.